RELIGIOUS AND MEDICAL MENTAL HEALTH CARE IN WESTERN AND EASTERN CONTEXT - - Subandi (Buletin Psikologi, 1998)
The fact that religion is not only concerned with spirituality and morality but also with psysical dan psychological health is reflected in the teaching of most religious traditions in the world.